Hormonal and metabolic responses to acute exercise in Thai women. - S. Chearskul (2018)
Physiological and hormonal changes after acute exercise of moderate intensity (75% VO2 max) by pedalling bicycle ergometer were studied during follicular and/or luteal phase of menstrual cycle in sixteen healthy Thai women compared to the other sixteen non-exercised women. Physiological recordings and hormonal determinations were performed at corresponding times as follows: before, immediately after and 30 minutes after stopping exercise. Exercise significantly increased lactic acid, pulse rate, respiratory rate, systolic and mean arterial blood pressure and decreased plasma glucose while diastolic blood pressure, hemoglobin and hematocrit were not significantly changed. Plasma LH, FSH and estradiol were unaffected by exercise either in follicular or luteal phase. Plasma progesterone and cortisol rose in response to acute exercise during luteal and follicular phase respectively. Testosterone and prolactin concentrations in blood decreased significantly 30 minutes after exercise during the luteal phase. The effects of acute exercise on studied hormones related to reproductive function in women were discussed.